Ash behavior during hydrothermal treatment for solid fuel applications. Part 2: Effects of treatment conditions on industrial waste biomass. (1st August 2016) - Mäkelä, Mikko; Yoshikawa, Kunio
Graphical abstract: Highlights: Effect of treatment conditions on composition and solubility of ash. Ash dissolution and yield governed by liquid pH and calcium carbonate solubility. Dissolution of calcium carbonate decreases ash fusion temperature during combustion. Decreasing the ash content of sludge can weaken ash properties for combustion. Abstract: This second half of our work on ash behavior concentrates on the effects of hydrothermal treatment conditions on paper sludge. Ash composition and solubility were determined based on treatment temperature, reactor solid load and liquid pH using experimental design and univariate regression methods. In addition, ash properties for combustion were evaluated based on recent developments on ash classification. Based on the results, all experimental variables had a statistically significant effect on ash yields. Only reactor solid load was statistically insignificant for char ash content, which increased based on increasing treatment temperature due to the decomposition of organic components. Ash dissolution and ash yield were governed by liquid pH and the generation of acids mainly due to the solubility of calcium carbonate identified as the main mineral species of paper sludge. Dissolution of calcium carbonate however decreased ash fusion temperatures more likely causing problems during char incineration. This indicated that decreasing the ash content of sludge during hydrothermal treatment can actually weaken ash properties for solid fuel applications.